A novel test of implicit memory; an eye tracking study - Jonathan CHUNG (International Journal of Applied Methods in Electronics and Computers, 2014)
Novelty preference in visual scanning behaviour is used to test implicit memory in patients with Alzheimer’s disease (AD). During the test, subjects are presented with slides that include both novel images and images that were seen before (repeated images). Slides are presented sequentially and the number of slides between the first and second presentations of repeated images is varied to mask the purpose of the test. The normalised average glance duration (N-AGD) on repeated images (the bias towards novelty) was used to measure novelty preference. Data from 10 young controls showed that the bias towards novelty is reduced as the number of slides between the first and second presentations of repeated images is increased. A group of 17 patients with AD showed no significant bias towards novelty while a group of 21 age matched controls do exhibit such bias (t(20) = 6.16, p < 0.001). The data suggest that patients with AD have no preference to novel images and support the idea that AD affects implicit memory. The receiver operator characteristics of the bias towards novelty showed that patients with AD and age-matched controls can be differentiated with both high sensitivity and high specificity.